Bacterial Infections in Cirrhosis. Issue 3 (17th September 2021) - Tonon, Marta; Angeli, Paolo; Piano, Salvatore
Abstract : Abstract: Bacterial infections are the most common trigger of acute decompensation of cirrhosis. The occurrence of infections in cirrhosis is associated with the development of organ dysfunctions, failures, and acute on chronic liver failure. The combination of infections and organ dysfunction/acute on chronic liver failure dramatically increases the mortality risk in these patients. Infections in cirrhosis are a big challenge for clinicians, since the mortality from sepsis is increasing in these patients worldwide. The rapid and progressive spread of multiresistant bacteria has been blamed for the increased mortality rate. Several studies have shown that early diagnosis and appropriate administration of antibiotic treatment are crucial for improving prognosis in these patients. Moreover, the prevention and treatment of acute kidney injury and organ failures are fundamental parts of management of infections in cirrhosis. Herein we provided a concise and updated review of the literature on bacterial infections in patients with cirrhosis.